2020
DOI: 10.3390/ijerph17165749
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices Related to Salt Intake among Saudi Adults

Abstract: In Saudi Arabia, data regarding salt-related knowledge and practices are still lacking. This cross-sectional study aimed to investigate salt-related knowledge and practices and associated factors in Saudi adults. Data on the following variables were collected from 467 participants living in Madinah or Jeddah via face-to-face interviews: demographics, anthropometrics (height and weight), blood pressure (assessed using a digital sphygmomanometer), salt-related knowledge, and practices related to salt intake. Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
9
0
3
Order By: Relevance
“…These countries include Egypt, Iran, Jordan, KSA, Lebanon, Morocco, Oman, Pakistan, Sudan, and the UAE. Most of the KAB surveys were based on questions relating to knowledge of the adverse health effects of high salt intake, attitudes towards the reduction of salt intake and its importance, as well as consumers’ behavior such as adding salt to food prior to tasting, or cooking with low-salt products [ 29 , 30 , 52 , 54 , 70 , 75 , 79 , 82 , 87 , 88 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These countries include Egypt, Iran, Jordan, KSA, Lebanon, Morocco, Oman, Pakistan, Sudan, and the UAE. Most of the KAB surveys were based on questions relating to knowledge of the adverse health effects of high salt intake, attitudes towards the reduction of salt intake and its importance, as well as consumers’ behavior such as adding salt to food prior to tasting, or cooking with low-salt products [ 29 , 30 , 52 , 54 , 70 , 75 , 79 , 82 , 87 , 88 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…The available few studies on salt-related attitude in the region have also revealed that only a small proportion of consumers were concerned about the amount of salt consumed in their diets [ 88 ]. At the same time, suboptimal practices were identified, with a small percentage of consumers reporting to check salt-related information on the food label [ 88 , 130 ], while the vast majority reported to add salt during cooking or at the table [ 52 , 79 , 88 , 126 , 127 , 131 , 133 , 134 , 140 ]. It is recommended that countries of the region consult these KAB findings when developing or further tailoring their consumer education initiatives in order to address culture-specific gaps in knowledge and attitude towards salt reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the consumer end, several cross-sectional studies conducted between 2019 and 2020 among adults and university students assessed their knowledge, attitude and behavior towards several dietary components, including SSF. The results revealed that participants had poor knowledge and an elevated consumption of salt, good knowledge of added sugar health risks, yet an elevated intake of sweets and fast foods and a low consumption of F&V [ 52 , 53 , 54 ]. An assessment among Saudi adults prior to the HFS implementation related poor fiber intake to the expensive prices of fruits and vegetables, limited availability and dislike of their taste [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding also supports those from a previous study reporting that people who are aware of the daily limit of salt intake are more likely to take action to reduce dietary salt consumption [ 20 ]. In Mongolia, people who consume salted suutei tsai consume significantly more salt on average [ 21 ]; thus, a focus on salted suutei tsai consumption may be important to reduce salt intake in this population, also because salt-related practices are negatively associated with sodium intake [ 22 ].…”
Section: Discussionmentioning
confidence: 99%